Perinatal Arterial Ischemic Stroke in Northern Queensland - Edmonds, Liza Kathleen; Kandasamy, Yoga; Lamont, Anthony; O'Connor, Sarah (American Journal of Perinatology, 2012)
Objectives Our objective was to review the occurrence, presentation, and associated risk factors of stroke in infants at a tertiary neonatal intensive care unit.Study Design Inpatient electronic records identified infants between March 2002 and March 2011 who had perinatal arterial ischemic stroke.Results Ten infants had perinatal arterial ischemic stroke, 50% were outborn, 20% were indigenous, and mortality was 30%. Median birth weight was 2970 g (range 1699 to 3443 g), and median gestation was 36 weeks (range 32 to 41 weeks). Perinatal arterial ischemic stroke were left sided in three, right sided in three, and bilateral in four. Presentation included four with seizures, four with apnea/sepsis, one with thrombosis, and one without symptoms. In 4 of 10 cases reported in this series, there was a maternal history of gestational diabetes, although the incidence of gestational diabetes in Australia is only 4.5%.Conclusion The incidence of gestational diabetes mellitus in our cases appears to be very much higher than the average population. Larger studies are needed to determine if gestational diabetes mellitus is a risk factor for perinatal arterial ischemic stroke.
Keywords: neonatal stroke; perinatal stroke risk factors; neonatal seizures; gestational diabetes mellitus